State with spontaneously broken time-reversal symmetry above the superconducting phase transition - Grinenko, Vadim; Weston, Daniel; Caglieris, Federico; Wuttke, Christoph; Hess, Christian; Gottschall, Tino; Maccari, Ilaria; Gorbunov, Denis; Zherlitsyn, Sergei; Wosnitza, Jochen; Rydh, Andreas; Kihou, Kunihiro; et al. (Nature Physics, 2021)
The most well-known example of an ordered quantum state—superconductivity—is caused by the formation and condensation of pairs of electrons. Fundamentally, what distinguishes a superconducting state from a normal state is a spontaneously broken symmetry corresponding to the long-range coherence of pairs of electrons, leading to zero resistivity and diamagnetism. Here we report a set of experimental observations in hole-doped Ba1−xKxFe2As2. Our specific-heat measurements indicate the formation of fermionic bound states when the temperature is lowered from the normal state. However, when the doping level is x ≈ 0.8, instead of the characteristic onset of diamagnetic screening and zero resistance expected below the superconducting phase transition, we observe the opposite effect: the generation of self-induced magnetic fields in the resistive state, measured by spontaneous Nernst effect and muon spin rotation experiments. This combined evidence indicates the existence of a bosonic metal state in which Cooper pairs of electrons lack coherence, but the system spontaneously breaks time-reversal symmetry. The observations are consistent with the theory of a state with fermionic quadrupling, in which long-range order exists not between Cooper pairs but only between pairs of pairs.
CRIS-Team Scopus Importer:2022-04-14